Inherent variability in airway characteristics of simulation manikins: is it time we standardised assessments of crisis management skills?. (18th August 2016) - Ashokka, Balakrishnan; Narendiran, Krishnasamy; Bhattacharya, Abhijit; Pai, Dinker; Liang, Shen; Subramanian, Shoba; Larmie, Ernest T; Chen, Fun Gee
Abstract : Introduction: Learning of simulation-based crisis management skills involves technologically advanced manikins and use of automated scenarios. Progressions in preprogrammed scenarios require finite task completion such as successful airway intubations for achieving optimal learning outcomes aligned to curricular goals. The study was set to explore the existing variability among various simulation manikins in use at our institute for undergraduate medical education. Methods: 56 final-year undergraduate students, who had received prior training in airway management skills, performed intubations on each of the 5 different manikins (56×5=280 intubations). The manikins used were the Human Patient Simulator (HPS), iStan & Emergency Care Simulator (ECS) from CAE Healthcare and Mega Code Kelly (MCK) and Airway Trainer (AWTR) from Laerdal. The students' performances were compared for success rates, ease of intubation, grade of laryngeal visualisation and presence of tooth injury on the manikins, Data from the intubations were cross-tabulated and evaluated by general estimating equation analysis using the Poisson model. Results: iStan had the higher rates of failure to intubate (64.3%). iStan (62.5%) and HPS (57.1%) had statistically significant teeth injury (p<0.0001) compared to other manikins. HPS and AWTR had the least difficult grades of laryngeal visualisation (Cormack Lehane grades 1 and 2), while the most difficult grade of visualisation (Cormack Lehane grades 3 and 4) was reported in ECS (44.6%). Conclusions: Each of the high-technology manikins used in automated scenarios for crisis management teaching and learning has heterogeneity in airway features. Since frequent airway management is a critical component of simulation scenarios, this can affect student performance when these manikins are used for formative and summative high-stakes assessments.